Implementasi Model Pembelajaran Berbasis Digital Dalam Kbm Di Man 2 Kota Sukabumi - Adji, Ardhiva Fachrul; Suryani, Lilis; Faaizah, Neng Lailatul; Andani, Rayhan Fadhlan (JURNAL MANAJEMEN PENDIDIKAN, 2025)
IMPLEMENTATION OF DIGITAL-BASED LEARNING MODEL IN KBM AT MAN 2 SUKABUMI CITYThis study aims to analyze the implementation of a digital-based learning model in the teaching and learning process (KBM) at MAN 2 Kota Sukabumi and to identify the supporting and inhibiting factors in its application. This research employs a qualitative approach with a descriptive method. Data collection was conducted through interviews with teachers and students, direct classroom observations, and document studies related to school policies on technology use in learning.The findings indicate that the implementation of digital-based learning at MAN 2 Kota Sukabumi is carried out through various platforms with the support of infrastructure and school policies. The supporting factors include internet access, interactive methods, and student enthusiasm, while the challenges involve device limitations, network issues, and gaps in technological skills. As an impact, students become more active and independent, but some still struggle with understanding the material and maintaining focus. To optimize this approach, improvements in infrastructure, training, and a combination of digital and face-to-face methods are necessary..